Are women really risk-averse? The lending behavior of women-owned banking cooperatives in India. Issue 6 (20th August 2018) - Ghosh, Saibal
Abstract : Purpose: The purpose of this paper is to examine the lending behavior of women-owned cooperatives (WoCs) by exploiting the natural experiment of the financial crisis, employing a novel data set of Indian cooperative banks during 2004–2013. Design/methodology/approach: In view of the longitudinal nature of the data, the authors employ panel data techniques for the purposes of analysis. Findings: The findings indicate that WoC banks increased lending to both agriculture and small-scale industries, especially in high-income states. Further disaggregation reveals that the possible weaknesses in asset quality from lending to these sectors in low-income states could be driving the results. Originality/value: To the best of our knowledge, this is one of the earliest studies for a leading emerging economy to empirically investigate the behavior of WoC banks and relatedly, how their behavior evolved during the financial crisis.